Coronavirus Disease-2019 Response–Global Public Health Professionals Supporting Collaborative, Official, Organized Actions in Local Communities - Gregory Fant; Elfatih M; Ednah Madu; Renu Tyagi; Sharath B. Nagaraja (Public Health – Open Journal, 2020)
In this special editorial we discuss the ways in which global public health professionals can support other public health, medical, laboratory, health education, and emergency management professionals responding to the coronavirus disease-2019 (COVID-19) pandemic. The World Health Organization (WHO) assigned a Global WHO Risk Assessment Level of “Very High” to the treatment of COVID-19.1 Globally, the responses of governments to COVID-19 have been containment and mitigation where the disease is present. On March 2nd, 2020, there were 88,948 confirmed cases. The number of cases has only increased since that time, and on March 11th, 2020, WHO declared COVID-19 as pandemic.2 As of March 26th, 2020,3 WHO has reported the following (see Table 1):